AICCRA-Senegal: Preparing for the 2024 agricultural campaign - Folorunso, M. Akinseye; Faye, Aliou; Diouf, Doudou; Zagré, Inoussa; Thiaw, Moussa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Over the past three years, the AICCRA project has played a vital role in improving the productivity of farmers in Senegal. This has been achieved through the widespread dissemination of Climate Information Services (CIS) and Climate Smart Agriculture (CSA) packages to support adaptation to the impacts of climate change. Capacity building of key stakeholders, including extension agents and lead farmers, is crucial for promoting the adoption of CSA practices to enhance sustainable food production. Stakeholders across clusters have received training and established demonstration plots to share their knowledge and experience. The project aims to scale up CIS and CSA technologies, expanding to more villages and regions, and this year a new cluster has been introduced in the region of Kaolack (Wack Ngouna). The recent pre-season training in five clusters allowed for feedback gathering and discussion on project outcomes with direct beneficiaries, emphasizing the importance of promoting climate resilient innovations in agriculture. This pre-season training spanned from June 12 to 22, 2024, across the five clusters (Meouane, Thiel, Koumpentum, Daga Birame and Wack Ngouna) and facilitated by the ICRISAT and CERAAS project team. The objective of this training is to equip the beneficiaries with relevant knowledge on the resilience of agricultural innovations and the dissemination of CSA practices and CIS in the selected clusters. To increase the productivity of target crops through the utilization and adoption of innovation across the intervention villages. Specific objectives include (1) reviewing and sharing the experience of the 2023 on-farm demonstration; (2) educating the beneficiaries on the importance and objectives of innovative trials and demonstrations across the villages; (3) Building Capacity of the field-level workers including ANCAR, CERAAS, locally trained supervisors for successful implementation of the designed protocol for demonstrations to achieve good results; and (4) use and benefits of climate-based advisories generated through the ISAT platform for decision-making. There were 103 participants who attended the training across the five clusters including lead farmers and other farmers representatives, ANCAR extension agents, field assistants, and facilitators (ICRISAT, ISRA-CRZ, ISRA-CERAAS) respectively. The training included (i) key achievements of AICCRA through participatory demonstration and extension, (ii) impacts of climate-smart management practices on pearl millet groundnut productivity and cowpea in Senegal, (iii) 2024 growing season demonstration and innovation, and (iv) dissemination of advice and climate information services in AICCRA project sites. Participants from the four existing clusters expressed their appreciation for the project's support during the 2022 and 2023 growing seasons, highlighting their satisfaction with the implemented technologies. Farmers from the new cluster in Wack Ngouna were introduced to the AICCRA project for the 2024 season. By the end of the training, they were well-informed about AICCRA and its objectives. The training proved to be highly educational and informative for all the farmers involved.